P99 Clinical characteristics and management of dual asthma and chronic obstructive pulmonary disease (copd) diagnosis in primary care; results from the welsh national copd primary care audit. (15th November 2017) - Fisk, M; McMillan, V; Brown, J; Holzhauer-Barrie, J; Khan, MS; Baxter, N; Roberts, CM
Abstract : Introduction: Asthma and COPD are two common conditions that are diagnosed and managed in primary care. However, it is currently unknown whether patients with a dual diagnosis of asthma and COPD differ from patients with COPD alone, based on UK general practice records. We sought to evaluate the clinical characteristics and management in primary care of patients with a dual diagnosis of asthma and COPD, compared to those with COPD alone, using data from the first Welsh national COPD primary care audit. Methods: The Welsh national COPD primary care audit prospectively collected data of patients registered with COPD from 61% of GP practices in Wales covering January 2014-March 2015. This analysis compared 5682 patients with a current co-diagnosis of asthma to 42 301 patients with COPD alone. Results: There were no significant differences in age (71±12 years for both), body mass index (27.54±6.40 vs 27.42±6.32 kg/m 2 ), gender (48% vs 47% female), or smoking status (33.1% vs 33.8% current smoker) between patients with a co-diagnosis of asthma vs patients with COPD alone, respectively. Spirometry, exacerbation frequency and reported breathlessness were also similar [(FEV1 : 1.49±0.64 vs 1.50±0.63 litres, p=0.65), (exacerbations: 7.36±8.41 vs 7.24±8.73, p=0.36), (MRC: 2.62±1.02 vs 2.59±1.01, p=0.10)]. However, patients with a co-diagnosis of asthma compared to COPD alone, were less likely to receive influenza vaccination (80.2% vs 81.4%, p<0.001), pulmonary rehabilitation (15.9% vs 18.9%, p<0.001), 3–6 month review (1.6% vs 2.6%, p<0.001) or smoking cessation (67.2% vs 68.4%, p=0.07), but were more likely to receive pharmacology therapies: long acting beta agonist (LABA): 28.8% vs 25.8%, p<0.001, inhaled corticosteroids (ICS): 51.7% vs 48.2%, p<0.001, long acting muscarinic antagonist: 69% vs 65.8%, p<0.001, and combined LABA/ICS inhaler: 70.6% vs 68.5%, p<0.001. Conclusions: Patients with a dual diagnosis of asthma and COPD compared to patients with COPD alone, received less non-pharmacological COPD management in primary care, despite being on more inhaled medication and having similar levels of COPD severity. These are clinically important data from the Welsh national COPD primary care audit and suggest that quality improvement actions focused on COPD care for patients with a dual diagnosis of asthma and COPD are required.